Optimized spray-drying of zinc sulfate-loaded liposomes: physicochemical characterization and in vitro release assessment - Monireh Abbassi; Samad Nejad Ebrahimi; Masoud Rahimi (Scientific Reports)
Abstract Zinc, a vital trace element plays a crucial role in various physiological functions, faces challenges in bioavailability due to dietary and pharmaceutical interactions. To enhance its delivery and stability, this study formulated spray-dried zinc sulfate-loaded liposomes using Maltodextrin as a stabilizing agent. Zinc-loaded liposomes were prepared via the thin-film hydration method and spray-dried under optimized conditions. The spray-dried liposomes exhibited a mean particle size of 18.35 ± 7.42 μm and a polydispersity index (PDI) of 0.32 ± 0.18, indicating size uniformity. A notably high encapsulation efficiency (EE%) of 88.24 ± 0.98% was achieved, demonstrating effective zinc entrapment. Thermal stability analysis revealed significant improvement, with TGA confirming enhanced structural integrity. XRD and FTIR analyses indicated successful encapsulation and interaction between zinc sulfate and phospholipids, while in vitro release studies showed sustained zinc release, with 94.98% cumulative release over 12 h compared with the rapid dissolution of free zinc sulfate. Stability tests over 90 days highlighted minimal changes in particle size (Δ = 0.22 μm) and EE% (Δ = 0.13%) under ambient storage conditions. These findings demonstrated the potential of spray-dried liposomes as an effective delivery system for zinc sulfate, offering enhanced stability and controlled release for pharmaceutical and nutraceutical applications.